The hypothalamic transcriptome reveals the importance of visual perception on the egg production of Wanxi white geese - Yang, Lei; Jia, Changze; Li, Yanzhong; Zhang, Yafei; Ge, Kai; She, Deyong (Frontiers in Veterinary Science, 2024)
Egg performance significantly impacts the development of the local goose industry. The hypothalamus plays an essential role in the egg production of birds. However, few potential candidate genes and biological functions related to egg production in geese have been identified in hypothalamus tissue. In this study, 115 geese were raised and observed for 5 months during the laying period. To understand the regulation mechanism of egg production, the hypothalamus transcriptome profiles of these geese were sequenced using RNA-seq. The hypothalamus samples of four high egg production (HEP) and four low egg production (LEP) geese were selected and collected, respectively. A total of 14,679 genes were identified in the samples. After multiple bioinformatics analyses, Gene Ontology (GO) annotations indicated that genes related to egg production were mainly enriched in biological processes of “response to light stimulus,” “sensory system development,” and “visual perception.” Six potential candidate genes (PDE6C, RHO, MFRP, F2, APOB, and IL6) based on their corresponding GO terms and interaction networks were identified. These identified candidate genes can be used as selection markers to improve the egg production of Wanxi white geese. Our study highlights how visual perception may affect the regulation of geese egg production.